Sodium hydrosulfide induces systemic thermotolerance to strawberry plants through transcriptional regulation of heat shock proteins and aquaporin - Christou, Anastasis; Filippou, Panagiota S.; Fotopoulos, Vasileios; Manganaris, George A. (My University, 2014)
Background: Temperature extremes represent an important limiting factor to plant growth and productivity. The present study evaluated the effect of hydroponic pretreatment of strawberry (Fragaria x ananassa cv. ‘Camarosa’) roots with an H2S donor, sodium hydrosulfide (NaHS; 100 μM for 48 h), on the response of plants to acute heat shock treatment (42°C, 8 h). Results: Heat stress-induced phenotypic damage was ameliorated in NaHS-pretreated plants, which managed to preserve higher maximum photochemical PSII quantum yields than stressed plants. Apparent mitigating effects of H2S pretreatment were registered regarding oxidative and nitrosative secondary stress, since malondialdehyde (MDA), H2O2 and nitric oxide (NO) were quantified in lower amounts than in heat-stressed plants. In addition, NaHS pretreatment preserved ascorbate/glutathione homeostasis, as evidenced by lower ASC and GSH pool redox disturbances and enhanced transcription of ASC (GDH) and GSH biosynthetic enzymes (GS, GCS), 8 h after heat stress imposition. Furthermore, NaHS root pretreatment resulted in induction of gene expression levels of an array of protective molecules, such as enzymatic antioxidants (cAPX, CAT, MnSOD, GR), heat shock proteins (HSP70, HSP80, HSP90) and aquaporins (PIP). Conclusion: Overall, we propose that H2S root pretreatment activates a coordinated network of heat shock defense-related pathways at a transcriptional level and systemically protects strawberry plants from heat shock-induced damage.
Keywords: Ascorbic acid; Heat shock proteins; Hydrogen sulfide; Nitrosative stress; Oxidative stress; Priming; Thermotolerance; Fragaria x ananassa